Throughfall data from the Mendaram peat swamp in Brunei Darussalam - Alexander R Cobb; Charles Franklin Harvey (PANGAEA, 2019)
The throughfall data are the average of data from four siphoning tipping-bucket rain gauges (Texas Electronics TR-525S, Dallas, Texas, USA) installed 50 cm above the peat surface along a 100 m transect, as described in Cobb and Harvey (2019). The coordinates provided for the throughfall measurements (in locations dataset) are the coordinates of the mid-point of the 4 throughfall gauges. The coordinates of the individual throughfall gauges were: Gauge 1: 114.354260, 4.370139 Gauge 2: 114.354034, 4.369900 Gauge 3: 114.353943, 4.369769 Gauge 4: 114.353661, 4.369449 The centroid of these 4 locations (recorded in locations dataset) was found by converting the coordinates of each gauge to a local projected coordinate system (GDBD2009, EPSG:5247), averaging the northing and easting coordinates, and converting back to longitude-latitude coordinates (EPSG:4326).
In supplement to: Cobb, AR; Harvey, CF (2019): Scalar Simulation and Parameterization of Water Table Dynamics in Tropical Peatlands. Water Resources Research, 55(11), 9351-9377, https://doi.org/10.1029/2019WR025411